Accident Occurrence and Functional Health Patterns. A Pilot Study of Relationships in a Graduate Population. - DE VRIES, JAN; SHEERIN, FINTAN; CURTIS, ELIZABETH (My University, 2012)
PURPOSE: This pilot study sought to examine the relationship between functional health patterns and accident proneness. METHODS: A quantitative-descriptive design was employed assessing accident proneness by collecting data on the occurrence of accidents among a sample of university graduates, and examining this in relation to biographical data and information collated using the Functional Health Pattern Assessment Screening Tool (FHPAST). Data were analyzed using descriptive and inferential statistics. FINDINGS: One FHPAST factor predicted more frequent sports accidents. Age was also shown to be a significant predictor but in a counterintuitive way, with greater age predicting less accident proneness. CONCLUSION: The FHPAST may have a role to play in accident prediction. IMPLICATIONS FOR NURSING PRACTICE: Functional health pattern assessment may be useful for predicting accidents.
PUBLISHED
Keywords: Accidents; Making Ireland